Tinjauan Filologi Kritis Manuskrip Al-Minhaj Al-Qowim Syarh Al-Muqadimah Al-Hadramiyyah Fasl Fi mawaqiti as-salati - Muhamad Agus Mushodiq (UIN Sunan Gunung Djati, 2020)
This paper aims to examine the book titled al-Minhaj al-Qowim Syarh al-Muqadimah al-Hadramiyyah in the article of fi mawaqiti as-salah on the basis of philological work which includes edits, transliteration, and translation of texts. This paper also aims to explore the meaning of the text using the speech act theory. In studying the text in philology, researchers use the standard edition single manuscript method. The translation method used is the literal method and the free method. In reviewing the meaning of the text, the researcher uses the speech act theory formulated by J. L. Austin including locution, illocution and perlocution. The results of this study are (1) In editing the text, the researcher found several errors in grammatical level, especially morphologically and the vowel error. (2) The text gives messages about the importance of praying at the beginning of time, some strict requirements about being allowed to end the time of prayer, (3) Prompts to pray at the beginning of time, both salat al-zuhr: midday, salat al-'asr: the late part of the afternoon, salat al-maghrib: just after sunset, salat al-'isha: between sunset and midnight (with notes), and salat al-fajr: dawn, (4) Invitations to hasten the implementation of salat al-maghrib, bearing in mind that the time interval between salat al-maghrib and salat al-'isha is very close together, especially in his explanation he also explained about the time that is forbidden in carrying out salat al-maghrib. (5) Regarding the salat al-'isha, he (Abdul Malik) invites Muslims to make two choices that are equally good, first: performing the evening prayer at the beginning of time, bearing in mind that the best practice is the prayer at the beginning of time, and second: carrying out the evening prayer in one-third of the night as described in a hadith, and (6) Inviting the audience / Muslims to perform the Fajr prayer at the beginning of time, given that the end of the salat al-fajr time is not the arrival of the salat al-zuhr but from the sunrise, and the dawn time is very short.